Constraints and varietal trait preferences of sorghum producers in South Africa - Mofokeng, M. A.; Shimelis, H.; Laing, M. D. (Journal of Tropical Agriculture, 2016)
The objective of this study was to determine sorghum production constraints and preferred traits of sorghum varieties ideal for the smallholder farming systems of Limpopo Province in South Africa. The study was conducted in four Municipalities within two selected districts known for their sorghum production. Data were collected through semi-structured questionnaires, group discussions, key-informants, pairwise ranking and transect walks involving 311 farmers. Results indicated that the most important sorghum production constraints were bird damage, parasitic weeds, drought stress and postharvest insect pests. The traits of sorghum varieties preferred by farmers were good taste, high yield, resistance to bird damage, insect pests (weevils), and diseases, early maturity and drought tolerance. The study serves as the basis for formulating research and development strategies for sustainable sorghum production and productivity by resource poor famers in these and similar environments.